علانية التقييم ودوره في تحسين الأداء بشركة توزيع الكهرباء و الغاز سونلغاز الأغواط - حليمة عاشور; مريم بن نعيجة; عبد الفتاح شتيح (My University, 2021)
This study aimed to know the extent to which the announcement of the evaluation results contributed to improving individual and collective performance in the Sonelgaz Corporation. It included the performance of human resources and performance in general, and the last chapter was devoted to the field study so that we relied on the questionnaire as a tool for the study, which was applied to a sample size of 30 individuals from the Sonelgaz Foundation, also relying on the descriptive approach and the use of the Spss program to analyze the data of the study, as its results showed a lack of interest The institution has a sufficient evaluation process, which is directly reflected in the level of performance.